PENYUTRADARAAN FILM GORESAN PENSIL: GESTURE SEBAGAI REPRESENTASI BUDAYA SUNDA - Fauziah, Ika; Abidin, Zainal (Institut Seni Indonesia Padangpanjang, 2024)
Goresan Pensil the movie tells about the main character who faces problems, the gesture of the main character will be shown in this movie. Gestures in this movie are shown through the representation of Sundanese culture. The object of creation in this movie is a scenario that tells of a high school boy named Deo who has painting skills and dreams of becoming an architect, but on the other hand his father has another wish which requires him to continue his father's dream of becoming a teacher. Because according to his father being a teacher is a very noble job. Deo refuses, because according to Deo being an Architect is also part of a noble job. The aesthetic concept of the creation of Goresan Pensil the movie is in optimizing the gesture of the main character by paying attention to the representation of Sundanese culture. The main character actors are able to communicate using nonverbal communication to emphasize what is conveyed and are able to communicate using gestures to convey a feeling, as well as to signify several gestures found in Sundanese culture.